Genetic characterisation of yam (Dioscorea species, Dioscoreaceae) using microsatellite markers - Ismail Nama, Shaalan (2016)
The influence of asexual propagation on the genetic diversity of yams is poorly understood. In tropical and subtropical regions, farming practices had unintended consequences and made it often impossible to distinguish wild yams from domesticated counterparts. This project aimed to investigate the ennobled yams, and specifically farmers’ impact on genetic divergence of Dioscorea alata, Dioscorea bulbifera, and Dioscorea cayenensis species. Forty-eight accessions were collected from Southwestern Ethiopia and South-west Malay Peninsula. Eighteen microsatellite markers developed by Tostain et al. (2006) were utilized to amplify marker loci from the leaves and tubers of yam accessions from Malaysia and Ethiopia (both cultivars and ennobled). The optimized annealing temperatures (Ta) and MgCl2 concentrations for the PCR amplification were determined. Eighteen primers succeeded in amplifying Dioscorea cayenensis accessions. However, Da1D08 primers failed in amplifying Dioscorea alata, and Dpr3B12, Da1D08, and Dab2E09 primers from the eighteen primers were not successful in amplifying Dioscorea bulbifera samples. Dioscorea cayenensis species had the best record in optimum annealing temperature (Ta) compared to Dioscorea alata and Dioscorea bulbifera species. The fragment size produced by Ym30, Da1A01, Da3G04, and Dpr3D12 markers incorporated with M13 FAM amplifying D. alata, D. bulbifera, and D. cayenensis species deployed in characterisation of the Dioscorea species that revealed a minor divergence between the three species. Moreover, the MgCl2 and M13 FMA influence on the PCR products was investigated and documented where the optimal annealing temperature (Ta) and fragment size of some Dioscorea species specimens were altered by the MgCl2 different quantity in the PCR protocol. In addition, a discussion of the yam’s physical characterisation, and the impact of traditional farming management in different ecological and ethno-linguistic regions are included.